Reducing methane emission through management of cattle population and grass land—A case study in different regions of Maharashtra - GOSWAMI, S N; MANDAL, D K; MANDAL, C (The Indian Journal of Animal Sciences, 2010)
Agriculture contributes about 20% of global greenhouse gases (GHGs). Among the agricultural processes, ruminant livestock emits the highest amount (59%) of GHG through enteric fermentation which needs reduction through maintaining optimum size of animal population as per carrying capacity of the grazing land (GLS) available in the region, apart from endeavoring development of concentrated feed stock. While estimating the emission potential of the animal population of Maharashtra, mathematical model for computing desired level of animal population at carrying of presently available GLS of regions namely Konkan, western Maharashtra, Marathwada and Vidarbha, has been developed. The high correlation coefficient of the developed models will help to estimate optimum size of ruminants in different regions as per carrying capacity of GLS at different methane emission level. The result also indicates that the highest GHG emission (5176.44 lakh kg/annum) occurs in Western Maharashtra, followed by Vidarbha and Marathwada. Although Vidarbha ranks second highest in methane emission, the need for reduction of animal population in percentage terms is the lowest due to non-over saturation of carrying capacity of GLS. The highest percentage reduction (60%) is needed for western Maharashtra as the area of the available GLS is less to support the present over size of ruminants.